ANALISIS PERHATIAN WANITA KARIR TERHADAP KEBERHASILAN PENDIDIKAN ANAK DALAM KELUARGA DI DUSUN SAWAGI KECAMATAN PATTALLASSANG KABUPATEN GOWA - Nurmila, Nurmila; Fadilah, Ratnawaty (Jurnal Pendidikan Teknologi Pertanian, 2017)
This research entitled " Analysis Career woman Attention Of The Success Of Child Education In Family In Sawagi Village Of Pattallassang District Of Gowa Regency." This research aims to know the influence of career woman attention to the success of children education strategy for career woman in dividing time to give attention to education children, the factors that support and inhibit for career women to give attention to children's education. The research method is using qualitative and quantitative approach, the data obtained through interview is processed by using qualitative data, while the data obtained through alternative questionnaire answers are processed by using quantitative descriptive approach, and test the analysis using SPPS.volume 20.0 progaram assistance. The result of the acquisition is that the concern for a mother who has a career in physical bentuik in medium category is mean 0,5 and attention in psychic form is in high category that is mean 3,40. Both forms of attention have a positive effect on the success of children's education. Because one aspect that improves the success of children in education is an external factor that one of them from the family. Similarly, the strategy for career women in dividing the time to give attention to the success of their children's education is for mothers whose career has cooperation with other family, and the factors that support a mother's attention are the talent and intelligence of the child itself, while the inhibiting factor consists of influence environment, media and talent as well as the intelligence of the child itself.